Family Values of Youth in Modern Socio-Demographic Situation in Russia - N. Kasarkina, Elena; Vladimirovna Solovieva, Tatiana; Asstimovna Bistiaykina, Dinara; Pankova, E.G.; Antipova, Alena А. (Calitatea Vieții, 2018)
The article deals with value orientations of youth in the sphere of family and relationships, which are influenced by various factors. The most significant factors are the dynamics of values in society, the model of parental family and socio-demographic situation in the country.It is important to study the formation of family values in the minds of young people, as young people’s perceptions about marriage and family sum up the past experience and create a prototype of the future family. The style of behavior in a family, sexual behavior, and marital status of youth is not isolated; it largely determines the demographic structure of the whole family, prospects of its development, the nature of the tasks and the problems, which it has to solve. Therefore, a study of trends in the development of marriage and family value orientations of youth, as well as the problems of family socialization relate to multiple areas of sociology: sociology of youth, sociology of family, sociology of culture, sociology of education. They are important to study not only in Russia, but also in world practice.